Advances in Corrosion and Protection of Materials - Antunes, Renato Altobelli (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As contemporary and emerging engineering applications demand increasingly high performance from metallic materials, research into their degradation in a variety of environments is a hot topic in the scientific community. This reprint is dedicated to providing the readership with an up-to-date overview of current corrosion research on different metallic materials (steels, aluminum alloys, magnesium alloys, and copper alloys), exploring fundamental and practical aspects related to corrosion mechanisms and protection methods to advance the current knowledge in this field. The content of this reprint provides new and insightful concepts to promote the development of optimized surfaces with high corrosion protection ability.